Effect of pH on Co‐precipitated Cu‐ZnO‐ZrO2 Catalysts Used in CO2 Hydrogenation: the Role of Zn‐malachite in the Precursors. Issue 1 (2nd February 2021) - Gao, W.; Qu, G.; Xu, M; Chang, S.; Na, W.
Abstract: A series of Cu–ZnO–ZrO2 catalysts were prepared at different pH by co‐precipitation method and tested for the synthesis of methanol by CO2 hydrogenation. The influence of pH on the phase formation of precursor, the average Cu particle size and the interaction among different elements were discussed in detail. The activity and selectivity of the catalysts were tested for hydrogenation of carbon dioxide to methanol. When the precipitation was conducted at pH = 8.0, in addition to aurichalcite, Zn‐malachite was obviously present in the precursor and the resulting catalysts were more active. It was found that the pH exerts its effect through altering the phase composition of the precursors. The present of Zn‐malachite in the precursors facilitates the formation of more intimate interdispersion of CuO and ZnO, and the smallest Cu particle after calcination and reduction.